2010
DOI: 10.1088/0957-4484/21/14/145601
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of superhydrophobic Bi2S3complex nanostructures

Abstract: In this paper, we report a biomolecule-assisted soft chemistry route for constructing complex Bi(2)S(3) nanostructures that exhibit controlled wetting behavior. The as-synthesized sample was characterized by x-ray diffraction (XRD), scanning electron microscopy (SEM), field emission SEM (FE-SEM), transmission electron microscopy (TEM), high-resolution TEM (HRTEM), Fourier transform infrared (FT-IR), Raman, x-ray photoelectron (XPS) and photoluminescence (PL). The Raman spectra indicate that the surface optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 70 publications
3
35
0
Order By: Relevance
“…7b. This indicated the presence of Bi 2 S 3 , SnS, and Sn 2 S 3 phases through the Raman bands at 107, 218, and 307 cm -1 , respectively [22][23][24][25], confirming the results of the XRD analysis.…”
Section: Raman Spectroscopysupporting
confidence: 79%
“…7b. This indicated the presence of Bi 2 S 3 , SnS, and Sn 2 S 3 phases through the Raman bands at 107, 218, and 307 cm -1 , respectively [22][23][24][25], confirming the results of the XRD analysis.…”
Section: Raman Spectroscopysupporting
confidence: 79%
“…The good agreement with the literature values supports the high purity of our metal chalcogenide nanostructures. [49][50][51][52][53][54][55][56][57] The size and morphology of the metal chalcogenide nanostructures are characterized by TEM in Figure 3. The particle size distribution of each sample, counted from 200 particles, is presented in Figure S5.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 1 are listed the crystalline structures and phases identified in the studied SnS:Bi compounds; the values for the corresponding lattice constants are also shown, which are in very close agreement with the data reported in JCPDS cards (# 039-0354 for SnS, # 014-0619 for Sn 2 S 3 , # 023-0677 for SnS 2 and # 017-0320 for Bi 2 S 3 ). It was found that the SnS films (x = 0) grow in the orthorhombic phase, while the films synthesized by sulfurization of a Sn and Bi (x = 0.3, x = 0.5, and x = 0.7) grow with a mixture of several phases it is one member of the metal chalcogenides group A V 2 B V I 3 , which begins to be widely studied because of their physical and chemical properties, suitable for the development of solar cells, luminescent devices, pigments, IR detectors, and thermoelectric devices [7,8].…”
Section: Optical and Structural Characterizationmentioning
confidence: 99%